Nilai-Nilai Akhlak dalam Novel Guru Aini Karya Andrea Hirata - Khaerunnisa, Khaerunnisa; Faznur, Lutfi Syauki; Meilinda, Liana (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2021)
Moral Values in Guru Aini Written by Andrea Hirata ABSTRAKPenelitian ini berisi tentang nilai-nilai Akhlak Al-Islam dan Kemuhammadiyahan dalam novel Guru Aini karya Andrea Hirata. Nilai akhlak menjadi fokus utama pada penelitian ini karena akhlak merupakan salah satu pondasi dasar dari sifat manusia yang sangat erat kaitannya dengan perilaku manusia dengan Tuhannya. Penelitian ini bertujuan untuk memperoleh pemahaman yang mendalam mengenai nilai-nilai akhlak berupa nilai takwa, tawakal, kejujuran, keikhlasan, sabar  dan syukur dari novel Guru Aini karya Andrea Hirata. Novel tersebut memiliki nilai akhlak yang perlu diterapkan dalam kehidupan bermasyarakat serta menjadi khazanah keilmuan berkaitan antara agama dan sastra. Penelitian ini menggunakan metode kualitatif dan pendekatan analisis isi. Metode kualitatif ini dapat menghasilkan data deskriptif berupa kata-kata tertulis atau atau isi komunikasi berupa percakapan, teks tertulis, dan fotografi. Simpulan dari hasil penelitian ini terdapat 6 kutipan dari nilai takwal, 14 kutipan nilai tawakal, 18 kutipan dari nilai kejujuran, 4 kutipan dari nilai keikhlasan, 1 kutipan dari nilai sabar, dan 14 kutipan dari nilai syukur. Kata kunci: Nilai-nilai akhlak, karya sastra, novelABSTRACTThis study contains moral values based on Al-Islam and Muhammadiyah in the novel Guru Aini by Andrea Hirata. The value of akhlak (moral) is the main focus of this research because it is one of the basic foundations of human nature which is very closely related to human behavior with God. This study aims to gain deep understanding of akhlak (moral) values in the form value of piety/morals, resignation/never giving up, honesty, sincerity, patience and gratitude from the novel Guru Aini by Andrea Hirata. The novel has a moral value that needs to be applied in social life and becomes a scientific treasure related to religion and literature. This research uses qualitative method and content analysis approach, this qualitative method can produce descriptive data in the form of written words or communication content in the form of conversation, written text, and photography. Conclusions from the results of this study there are 6 quotes from the value of piety/morals, 14 quotes from the value of resignation / never give up, 18 quotes from the value of honesty, 4 quotations from the value of sincerity, 1 quote from the value of patience, and 14 quotes from the value of gratitude.Keywords: Akhlak (moral) value, literature, novelThis study contains moral values based on Al-Islam and Muhammadiyah in the novel Guru Aini by Andrea Hirata. The value of akhlak (moral) is the main focus of this research because it is one of the basic foundations of human nature which is very closely related to human behavior with God. This study aims to gain deep understanding of akhlak (moral) values in the form value of piety/morals, resignation/never giving up, honesty, sincerity, patience and gratitude from the novel Guru Aini by Andrea Hirata. The novel has a moral value that needs to be applied in social life and becomes a scientific treasure related to religion and literature. This research uses qualitative method and content analysis approach, this qualitative method can produce descriptive data in the form of written words or communication content in the form of conversation, written text, and photography. Conclusions from the results of this study there are 6 quotes from the value of piety/morals, 14 quotes from the value of resignation / never give up, 18 quotes from the value of honesty, 4 quotations from the value of sincerity, 1 quote from the value of patience, and 14 quotes from the value of gratitude.